2015
DOI: 10.5613/rzs.44.3.3
|View full text |Cite
|
Sign up to set email alerts
|

Cultural Consumption and Musical Preferences of Youth: Development of Typology in the Case of Zadar

Abstract: U radu se analiziraju i interpretiraju rezultati istraživanja kulturne potrošnje mladih u Zadru. U prvome dijelu rada izlažu se najvažniji teorijski pristupi kulturnoj potrošnji te se iznosi pregled prethodnih istraživanja kulturne potrošnje i životnih stilova mladih u Hrvatskoj. U središnjem dijelu rada iznose se i analiziraju rezultati istraživanja provedenog internetskom anketom 2014. godine na prigodnom uzorku mladih u Zadru (N = 429). Kako bi se ispitala struktura ispitanih kulturnih i glazbenih preferenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Based on the assumption that cultural participation entails an interest in cultural activities and content, investigating the interested audience can provide insights into potential disparities in motivation and frequency of participation in cultural activities and content. Previous studies on cultural participation, including Adamović (2017), Tonković, Marcelić and Krolo (2017) and Tonković et al (2014), have established a correlation between higher education and participation in high culture, as well as a correlation between economic capital and participation in cultural content. These studies have also found a correlation between residential status and frequency of participation in cultural content at the regional level but not at the urban level.…”
Section: Resultsmentioning
confidence: 91%
“…Based on the assumption that cultural participation entails an interest in cultural activities and content, investigating the interested audience can provide insights into potential disparities in motivation and frequency of participation in cultural activities and content. Previous studies on cultural participation, including Adamović (2017), Tonković, Marcelić and Krolo (2017) and Tonković et al (2014), have established a correlation between higher education and participation in high culture, as well as a correlation between economic capital and participation in cultural content. These studies have also found a correlation between residential status and frequency of participation in cultural content at the regional level but not at the urban level.…”
Section: Resultsmentioning
confidence: 91%
“…Considerations arise regarding the communication, in digital form and largely via the Web, of traditional music as a part of cultural heritage. This is a fairly new field that opens up possibilities to study, and contribute to, the development of critical discourse concerning the application of new technologies in communicating traditional music (Tonković et al, 2014). In contrast, modern music and its subforms, adjusted to global values and tastes, are entering rural regions.…”
Section: Music In the Tourism Offering Of Rural Regionsmentioning
confidence: 99%